2015
DOI: 10.1212/nxi.0000000000000162
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating more naturalistic outcome measures

Abstract: Objective:In this cohort of individuals with and without multiple sclerosis (MS), we illustrate some of the novel approaches that smartphones provide to monitor patients with chronic neurologic disorders in their natural setting.Methods:Thirty-eight participant pairs (MS and cohabitant) aged 18–55 years participated in the study. Each participant received an Android HTC Sensation 4G smartphone containing a custom application suite of 19 tests capturing participant performance and patient-reported outcomes (PRO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
40
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(43 citation statements)
references
References 16 publications
3
40
0
Order By: Relevance
“…A recent large-scale study demonstrated that more than 95% of people with multiple sclerosis have access to a mobile device and most use it routinely [10]. Recently published studies have described the use of technologies in developing tools to assess people with multiple sclerosis [7,9,11-13]. In a recent study, it was reported that both healthy participants and people with multiple sclerosis were capable of completing daily tasks on a smartphone for 1 year [7].…”
Section: Introductionmentioning
confidence: 99%
“…A recent large-scale study demonstrated that more than 95% of people with multiple sclerosis have access to a mobile device and most use it routinely [10]. Recently published studies have described the use of technologies in developing tools to assess people with multiple sclerosis [7,9,11-13]. In a recent study, it was reported that both healthy participants and people with multiple sclerosis were capable of completing daily tasks on a smartphone for 1 year [7].…”
Section: Introductionmentioning
confidence: 99%
“…Although there was a modest reduction in the number of people providing valid accelerometer data (≥1 week per month) during the study, as depicted in Figure 1A, adherence to and use of the accelerometer was higher than might be expected from surveying the literature in the general population 27,28 or among individuals with MS. 29 Proactive study management strategies might account for the relatively favorable retention rate in our study. It will be important for future studies to optimize monitoring strategies and retention for this critical subset of patients with MS.…”
Section: Discussionmentioning
confidence: 80%
“…Measuring neurological functions by patients via smartphones ( 6 8 ) may pose a solution for all aforementioned problems, while additionally empowering patients for greater participation in their neurological care. We have previously found comparable sensitivity and specificity of simple, smartphone-amenable measurements of finger and foot taps to 9HPT and 25FW, respectively ( 9 ).…”
Section: Introductionmentioning
confidence: 99%